A new species of Ischaemum L. (Poaceae) from Kerala, India (Bangladesh Journal of Plant Taxonomy, 2017)
Ischaemum sreenarayanii, a new species of Ischaemum L. is described andillustrated with detailed notes on distribution, conservation status and phenology. The new species is similar to I. santapaui and I. nairii but differs in number of attributes having up to 1.3 cm long filiform tip of the leaf apex, villous pseudopetiole of upper leaves and 4-6 conspicuous annular transverse ridges and winged margins of the sessile spikelet.Keywords: Ischaemum; New species; Poaceae; Kerala; India.Bangladesh J. Plant Taxon. 24(1): 3338, 2017 (June)